Pengaruh Corporate Social Responsibility (CSR) dan Good Corporate Governance (GCG) Terhadap Nilai Perusahaan: Studi pada PT Semen Indonesia Tbk Periode 2019-2024 - Rafi Rasendriya; Dwi Ermayanti Susilo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
From 2019 to 2024, this research will examine how PT Semen Indonesia Tbk's CSR and Good Corporate Governance initiatives impacted the company's stock price. “Using secondary data collected from the company's sustainability reports and annual reports, this study used a quantitative technique. Descriptive statistics, tests of classical assumptions, multiple linear regression, tests of hypotheses using t-tests and F-tests, and examination of coefficients of determination were all part of the data analysis process. The results show that CSR and GCG do not significantly impact business value, at least in part. In addition, PT Semen Indonesia Tbk's company value is unaffected by CSR and GCG at the same time. According to these results, financial performance, industry circumstances, macroeconomic variables, and social responsibility efforts are not the only determinants of company value gains; corporate governance procedures and social responsibility also play a role.” As a foundation for future studies on the factors that determine a company's worth, this one should help businesses improve their CSR and GCG initiatives.